2004
DOI: 10.2139/ssrn.587461
|View full text |Cite
|
Sign up to set email alerts
|

Monetary and Fiscal Policy Switching

Abstract: Abstract. A growing body of evidence finds that policy reaction functions vary substantially over different periods in the United States. This paper explores how moving to an environment in which monetary and fiscal regimes evolve according to a Markov process can change the impacts of policy shocks. In one regime monetary policy follows the Taylor principle and taxes rise strongly with debt; in another regime the Taylor principle fails to hold and taxes are exogenous. An example shows that a unique bounded no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 64 publications
2
21
0
Order By: Relevance
“…Linear methods can fail to capture this correlation, leading the approximations to incorrectly classify existence and uniqueness of equilibrium. Appendices in Davig, Leeper, and Chung (2004) show this in detail for two different linearization methods.…”
Section: A Benchmark Specificationmentioning
confidence: 99%
“…Linear methods can fail to capture this correlation, leading the approximations to incorrectly classify existence and uniqueness of equilibrium. Appendices in Davig, Leeper, and Chung (2004) show this in detail for two different linearization methods.…”
Section: A Benchmark Specificationmentioning
confidence: 99%
“…It is important to recognize that the assumption that …scal policy follows a rule with timeinvariant parameters is an assumption. Even if we found that the response of the primary surplus to lagged debt were too small for both eigenvalues to be within the unit circle, the monetary authority could still control the price level if the government were expected to adjust the primary surplus in the future in some way that di¤ers from the current estimated rule (Davig, Leeper, Chung 2007). However, promises of future changes to resolve current insolvency might not be credible.…”
Section: Stability and Dynamics In Equilibriummentioning
confidence: 87%
“…2, indicate that both tests reject the null hypothesis of no cointegration at the 5 percent level. 21 Pedroni's tests provide strong evidence that s it and b it are cointegrated and that s it and y it are also cointegrated.…”
Section: Fiscal Policy In the European Monetary Unionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under a linear rule, the future marginal response of the primary surplus is assumed to be the same as the historical marginal response. Davig et al () argued that there are regime shifts over different periods in the United States. Similarly, Lloyd‐Ellis and Zhu () argued that there was a change in the fiscal policy of the Canadian government in the mid‐1990s when debt was elevated.…”
Section: Model Applied: the Case Of Canadamentioning
confidence: 99%